Design and synthesis of metal-organic frameworks for applications in catalyzing organic chemical reactions - Thai, Jonathan E., author; Reynolds, Melissa M., advisor; Henry, Charles S., committee member; Farmer, Delphine K., committee member; Zabel, Mark D., committee member (Colorado State University. Libraries, 2022)
Metal-organic frameworks (MOFs) are versatile materials that possess a lot of potential for use as heterogeneous catalysts. Their crystalline structure creates a uniform, well-defined, highly porous framework that has a high density of active sites. Furthermore, their unprecedented tunability has allowed scientists to create several thousands of unique MOF structures. This has made MOFs a prominent area of research as they provide a clear path to move from homogeneous catalysis into heterogeneous catalysis. Heterogeneous catalysts are of utmost importance in the modern chemicals industry, playing key roles in the production of both organic and inorganic compounds. Heterogeneous catalysts help create lower energy pathways that allow for the catalysts to be more easily recovered and recycled (relative to homogeneous catalysts) and can enable more efficient production on large scale chemical production. However, MOFs have yet to be seen in widespread use for this purpose despite the many advantages they possess and the large variety of available MOFs due to their limitations, typically their lack of stability at high temperatures (most MOFs are typically only stable up to temperatures around 350-400°C). This dissertation works towards improving current MOFs for heterogeneous catalysis and using MOFs as heterogeneous catalysis in a continuous flow reactor. Chapter 1 of this dissertation provides a discussion on the background of MOFs, how they are made, their limitations as heterogeneous catalysts, the advantages they bring to the field of heterogeneous catalysis, and some of the key techniques used to characterize MOFs. Chapters 2 and 3 focus on the synthesis and development of CuBDTri (where H2BDTri = 1,4-1H-1,2,3-triazol-5-yl)benzene), the first Cu-based MOF nanosheet (MOFN) that is water stable and shown to be more catalytically active for the release of nitric oxide from S-nitrosoglutathione relative to CuBTTri (where H3BTTri = 1,3,5-tris(1H-1,2,3-triazol-5- yl)benzene). Chapter 2 focuses on how CuBDTri was originally designed, synthesized, and confirmed to be a newly created MOF. Chapter 3 then focuses on the work done to optimize the synthetic process used to make CuBDTri so that the resulting MOFN particles are as thin as possible, maximizing their efficiency as heterogeneous catalysts on a per-total-Cu-atom basis. Chapter 4 originally aimed to develop a continuous flow process using the MOF CuBTC (where BTC = benzene-1,3,5-tricarboxylate) to catalyze the Friedländer synthesis. However, over the course of this work, it was found that the conditions being used to perform the Friedländer synthesis resulted in the breakdown of the CuBTC and so efforts were redirected to determine what caused this breakdown and the identity of the active catalyst in this reaction system. The data provided in this chapter track the breakdown of CuBTC by the Friedländer synthesis and provide evidence towards what the catalyst identity is. Chapter 5 takes what was learned from Chapter 4 to transfer a condensation reaction to produce xanthene derivatives under continuous flow conditions, catalyzed by CuBTC. The results from the work completed here suggest that the reaction is being successfully performed under continuous flow conditions and is producing the desired xanthene. Furthermore, the success of this system provides further insight and understanding towards why CuBTC breaks down in the conditions used for the Friedländer synthesis in Chapter 4 but is stable under the conditions used to perform the condensation reaction in this chapter.
Keywords: flow; metal-organic frameworks; catalysis; nanosheets; heterogeneous